Sourcebook for Land Use, Land-Use Change and Forestry Projects - Pearson, Timothy; Walker, Sarah; Brown, Sandra (World Bank, Washington, DC, 2014)
This sourcebook is designed to be a guide for developing and implementing land use, land-use change and forestry (LULUCF) projects for the BioCarbon Fund of the World Bank that meet the requirements for the Clean Development Mechanism (CDM) of the Kyoto Protocol. Only project types and carbon pools that are eligible for credit under the CDM during the first commitment period (2008-2012) are covered. With its user-friendly format, the sourcebook introduces readers to the CDM processes and requirements, and provides methods and procedures to produce accurate and precise estimates of changes in carbon stocks. The sourcebook is not designed as a primer on field measurement tech-niques, although guidance is given. The sourcebook is intended as an addition to the Intergovernmental Panel on Climate Change (IPCC) good practice guidance on land use, land-use change and forestry (2003), providing additional explanation, clarification and enhanced methodologies. It is designed to be used alongside the good practice guidance.